Molecular Epidemiological Survey of Glucose-6-Phosphate Dehydrogenase Deficiency and Thalassemia in Uygur and Kazak Ethnic Groups in Xinjiang, Northwest China. (3rd May 2016) - Han, Luhao; Su, Hai; Wu, Hao; Jiang, Weiying; Chen, Suqin
Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency and thalassemia occur frequently in tropical and subtropical regions, while the prevalence of relationship between the two diseases in Xinjiang has not been reported. We aimed to determine the prevalence of these diseases and clarify the relationship between genotypes and phenotypes of the two diseases in the Uygur and Kazak ethnic groups in Xinjiang. We measured G6PD activity by G6PD:6PGD (glucose acid-6-phosphate dehydrogenase) ratio, identified the gene variants of G6PD and α- and β-globin genes by polymerase chain reaction (PCR)-DNA sequencing and gap-PCR and compared these variants in different ethnic groups in Xinjiang with those adjacent to it. Of the 149 subjects with molecular analysis of G6PD deficiency conducted, a higher prevalence of the combined mutations c.1311C > T/IVSXI + 93T > C and IVSXI + 93T > C, both with normal enzymatic activities, were observed in the Uygur and Kazak subjects. A case of rare mutation HBB : c.135delC [codon 44 (−C) in the heterozygous state], a heterozygous case of HBB : c.68A > G [Hb G-Taipei or β22(B4)Glu→Gly] and several common single nucleotide polymorphisms (SNPs) were found on the β-globin gene. In conclusion, G6PD deficiency with pathogenic mutations and three common α-thalassemia (α-thal) [– – SEA, −α 3.7 (rightward), −α 4.2 (leftward)] deletions and point mutations of the α-globin gene were not detected in the present study. The average incidence of β-thalassemia (β-thal) in Uygurs was 1.45% (2/138) in Xinjiang. The polymorphisms of G6PD and β-globin genes might be useful genetic markers to trace the origin and migration of the Uygur and Kazak in Xinjiang.